Performance Budgeting – the Slovenian Experience - Maja Klun (Central European Public Administration Review)
Reform processes in the public sector include measures leading to greater transparency in public spending, greater public accountability, and measurement of efficiency and effectiveness in the public sector. These measures include results-oriented budgeting, or a focus on results, or performance budgeting. This method of monitoring spending requires budget-spending units to set priorities and plan spending over the long term. The purpose of this paper is to define the concept and provide a brief presentation of various approaches to performance budgeting in practice abroad and the development of the budget process in Slovenia, measures relating to the implementation of performance budgeting, and the realisation of those measures.